(untitled) (European Journal of Formal Sciences and Engineering, 2022)
Over the last decades, the evolution of technology has helped us to facilitate various types of works in areas related to land and property management as well as spatial planning. The exploitation of new tools and methods has prompted the international interest in the recording and modeling of geospatial information in more than two dimensions depicted in traditional projects, until then. This has contributed to address a series of issues related to intense urbanization, as well as challenges in identifying complex ownership and building structures. A relatively recent such method is the mapping of buildings and wider spatial units by using Unmanned Aerial Vehicles (UAVs) that has contributed to the production of 3D models by using the appropriate software. This technology finds resonant in recent years in Greece. However, it has not been applied to the mapping of large spatial units such as urban areas. This research paper performs a wide area mapping using UAV. Its purpose is to investigate to what extent the UAVs can do it successfully. For this reason, a brief evaluation is attempted, taking into account the accuracy of the data as well as the cost and time required in relation to traditional techniques. The result justifies the specific technique that appears to produce good quality metering and quality data while helping to save resources.